Biochemical Profile of Multiple Myeloma in the Patients Visiting BPKIHS as Diagnosed by Agarose Gel Electrophoresis - Nepal, AK; Shakya, PR; Gelal, B; Das, BK Lal; Shrestha, BP; Lamsal, M; Baral, N; Majhi, S (Health Renaissance, 2011)
Multiple myeloma is a proliferative disease of plasma cells. The incidence of the disease increases with age. Objectives : To study different biochemical parameters and serum agarose gel electrophoresis patterns of patients consistent with clinical symptoms of multiple myeloma. Subject and Methods : A retrospective study was carried out in Department of Biochemistry, B.P. Koirala Institute of Health Sciences, from October 2008 to September 2009. Patients consistent with the symptoms of multiple myeloma were selected for the study. Alkaline phosphatase, total calcium, albumin and globulin levels were estimated. Bence Jones Protein, cell counts of bone marrow and x-ray of skull was carried out. Agarose gel electrophoresis was performed at buffer pH 8.6, 5 mili ampere current and the constant voltage of 200 volts was applied. Results : Serum electrophoresis patterns in all the patients showed M-Protein band (M-band) at gamma-region. Serum alkaline phosphatase levels were 216.0 ± 35.7 . Serum total calcium levels were 10.0± 1.5, serum albumin levels were 4.1 ± 0.5 and serum globulin levels were 3.7 ± 0.9 respectively. Bence Jones Protein was present in urine of the 7 patients out of 14. Plasma cell counts were more than 10% and lytic lesions on skull were present. Conclusion : Patients with multiple myeloma showed consistently increased total calcium, decreased serum albumin and normal alkalline phosphatase levels. Electrophoretic patterns showed M-band in all the patients, giving the confirmation of the diagnosis. Though a conventional technique, electrophoresis remains as the gold standard for the diagnosis of multiple myeloma. Health Renaissance, May-Aug 2010; Vol 8 (No.2):122-125